2008
DOI: 10.1002/jnr.21712
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase 2A–negative regulation of the protective signaling pathway of Ca2+/CaM‐dependent ERK activation in cerebral ischemia

Abstract: Extracellular-signal-regulated kinase (ERK) undergoes rapid inactivation following the intense activation evoked by cerebral ischemia and reperfusion. However, the precise mechanism of this inactivation has not been elucidated. To investigate how phosphatases regulate the ERK cascade following ischemia, the PP2A inhibitors cantharidin and okadaic acid were administrated to the CA1 subregion of the rat hippocampus. The resulting sustained ERK activity implies that PP2A is a major phosphatase contributing to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…In fact, death of CA1 pyramidal cells has been demonstrated to be an immediate result of ischaemia [34], though it has been reported that the majority of cells at the borders of the infarct were not yet dead after 48 hours [32]. In the current study, it was found that BA acted on calcium ion (Ca 2+ )-dependent signalling cascades, shown to play a neuroprotective role in cerebral ischaemia by signalling Ca 2+ /CaM-dependent ERK activation, and this is consistent with previous findings [35]. In 1999, Lipton noticed that extracellular Ca 2+ concentration sharply declines in the ischemic core immediately after ischaemia with a concomitant rise in extracellular potassium ions (K + ) ( ∼ 70 mM) over 2 hours and returns to near normal concentration over 6 to 24 hours [31].…”
Section: Discussionsupporting
confidence: 92%
“…In fact, death of CA1 pyramidal cells has been demonstrated to be an immediate result of ischaemia [34], though it has been reported that the majority of cells at the borders of the infarct were not yet dead after 48 hours [32]. In the current study, it was found that BA acted on calcium ion (Ca 2+ )-dependent signalling cascades, shown to play a neuroprotective role in cerebral ischaemia by signalling Ca 2+ /CaM-dependent ERK activation, and this is consistent with previous findings [35]. In 1999, Lipton noticed that extracellular Ca 2+ concentration sharply declines in the ischemic core immediately after ischaemia with a concomitant rise in extracellular potassium ions (K + ) ( ∼ 70 mM) over 2 hours and returns to near normal concentration over 6 to 24 hours [31].…”
Section: Discussionsupporting
confidence: 92%
“…We found upregulation of two raf kinase inhibiting proteins following Aβ treatment, namely phosphatidylethanolamine-binding protein 1 or Raf kinase inhibitor protein (RKIP) and protein phosphatase 2A (PP2A) [68,69]. The possible inactivation of ERK1/2, p38 or JNK pathways is in contrast to some studies reporting Aβ-induced pathological activation of raf pathways [70,71].…”
Section: Discussionmentioning
confidence: 99%
“…Raf-1 phosphorylation at Ser289/296/301 and ERK activity were apparently increased by inhibition of PP2A. Previous studies have demonstrated that ERK can be dephosphorylated by PP2A [18,19]. Therefore, we speculated that PP2A may dephosphorylate Raf-1 at Ser289/296/301 through two pathways: direct dephosphorylation of Ser289/ 296/301 and indirect inhibition of ERK inhibition.…”
Section: Discussionmentioning
confidence: 85%
“…Phosphorylation of those sites would induce Raf-1 to enter an inactive and desensitized state [15]. The Ser/Thr specific protein phosphatase 2A (PP2A) is also known to play a key role in regulating the Raf/MEK/ERK cascade [16][17][18][19]. It was thought that hyperphosphorylation of Raf-1 can be dephosphorylated by PP2A with the help of peptidylprolyl cis/trans isomerase Pin1 (protein interacting with NIMA -1).…”
Section: Introductionmentioning
confidence: 99%